The Integration of Europe: The Study of Econolllic and Political· Integration in International Business - Hadi, Achmad Setyo (Forum Manajemen; Vol 12 No 67 (1998): Forum Manajemen Prasetiya Mulya | Desember 1998- Januari 1999, 1998)
On January 1, 1993, the 12 member-states of the European Union (EU) implemented the Single European Act (the EU was expanded from 12 to 15 members on January 1, 1996). This act mandated the removal of all frontier controls between EU countries, thereby abolishing delays and reducing the resources required for complying with trade bureaucracy. The act was the logical culmination of the 35-year history of this trading bloc, which has progressively reduced barriers to the free flow of goods, services, and factors of production between its member-states. With the implementation of the Single European Act, the EU became a single market of 340 million consumers.